Pengaruh Impulse Buying, Harga Dan Penggunaan Shopee Paylater Terhadap Keputusan Pembelian (Studi Kasus pada Mahasiswa Fakultas Ekonomi dan Bisnis Angkatan 2019-2020 di Universitas Islam Malang) - Widiawati Susanti; Ronny Malavia Mardani; Andi Normaladewi (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract  This study aims to determine "The Effect of Impulse Buying, Price, and Use of Shopee Paylater on Purchasing Decisions (Case Study on Students of the Islamic University of Malang, Faculty of Economics and Business, Class of 2019-2020)". This study is classified as quantitative research. The researchers employed purposive sampling, employing the Slovin formula to determine the sample size, resulting in 95 respondents. Data collection was conducted through a questionnaire distributed via Google Forms, while data analysis involved the use of multiple linear regression analysis. The results showed that Impulse Buying, Price and Use of Shopee Paylater had a significant effect on Purchasing Decisions. Keyword: Impulse Buying, Price, and Use of Shopee Paylater on Purchasing Decisions.